A deformation-induced strengthened Cu-Cr-Nb heterostructure composite material and preparation method thereof
By introducing Cu regions into the Cu-Cr-Nb alloy matrix to build a heterogeneous microstructure, the problems of high cost and low yield strength of Cu-Cr-Nb alloys are solved, and the matching of strength and plasticity and excellent electrical conductivity are achieved. .
Patent Information
- Application Number
- CN202411194418.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-08-29
AI Technical Summary
The high cost and low yield strength of Cu-Cr-Nb alloys limit its further development and application in the electronics industry and other fields.
By introducing Cu regions into the Cu-Cr-Nb alloy matrix, a heterogeneous microstructure is constructed, and the strength difference is used to trigger heterogeneous deformation-induced strengthening, thereby improving the yield strength and work hardening ability.
A good match between the strength and plasticity of the Cu-Cr-Nb heterostructure composite material is achieved, while maintaining excellent electrical conductivity and reducing material preparation costs.
Smart Images

Figure CN118703830B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal composite materials, and in particular relates to a deformation induced strengthened Cu-Cr-Nb heterostructure composite material and a preparation method thereof. Background Art
[0002] Cu-Cr-Nb alloys have been widely used in many fields such as electronics industry, liquid rocket engines, rail transportation, electronic communications and navigation control, as well as materials that need to work at room temperature due to their excellent thermal properties and high temperature creep resistance. However, Cu-Cr-Nb alloys are relatively expensive and have low yield strength, which limits the further development and application of this material.
[0003] The study found that heterogeneous structural materials have excellent properties that traditional homogeneous materials do not have. Heterogeneous structural materials are composed of ductile and hard zones with significant differences in flow stress, which leads to strain distribution. The ductile zone bears a larger proportion of applied strain than the hard zone. At the same time, a strain gradient is formed near the interface between the ductile zone and the hard zone to adapt to the strain distribution, which requires geometrically required dislocations (GNDs) to adjust, resulting in heterogeneous deformation-induced strengthening. Experiments show that back stress can simultaneously improve the yield strength and work hardening ability of metal materials, thereby achieving a good match between material strength and plasticity. Summary of the invention
[0004] The purpose of the present invention is to overcome the deficiencies in the above-mentioned prior art and provide a deformation induced strengthened Cu-Cr-Nb heterostructure composite material. The composite material introduces a Cu region into a Cu-Cr-Nb alloy matrix, so that heterogeneous deformation induced strengthening is generated inside the prepared Cu-Cr-Nb heterostructure composite material, while ensuring good plasticity, the yield strength and work hardening ability of the Cu-Cr-Nb heterostructure composite material are improved, and a good match between the strength and plasticity of the Cu-Cr-Nb heterostructure composite material is achieved.
[0005] To achieve the above-mentioned purpose, the technical solution adopted by the present invention is: a deformation induced strengthened Cu-Cr-Nb heterostructure composite material, characterized in that it is composed of the following mass percentage regions: a Cu-Cr-Nb alloy region is 50% to 95%, and a Cu region is 5% to 50%.
[0006] The present invention introduces micron-sized Cu grains into the interior of the Cu-Cr-Nb matrix of the high-density precipitation phase through the strategy of constructing a heterogeneous microstructure. Due to the obvious strength difference between the Cu-Cr-Nb alloy region and the Cu region, uneven deformation occurs between the Cu-Cr-Nb alloy region and the Cu region, resulting in the development of back stress and positive stress of the Cu-Cr-Nb heterogeneous structure composite material, as well as strengthening and additional work hardening, which greatly improves the yield strength of the Cu-Cr-Nb heterogeneous structure composite material and effectively overcomes the problem that the strength and plasticity of the material of the uniform structure restrict each other. Generally speaking, strength and conductivity are contradictory, and increasing strength will reduce conductivity. However, the present invention introduces a Cu region into the Cu-Cr-Nb alloy region, utilizing the characteristic that the conductive performance of Cu is better than that of Cu-Cr-Nb, and the introduced micron-sized Cu grains provide a fast channel for electron transmission, so that the Cu-Cr-Nb heterogeneous structure composite material also has excellent conductivity.
[0007] At the same time, the present invention also discloses a method for preparing the above-mentioned deformation induced strengthened Cu-Cr-Nb heterostructure composite material, characterized in that the method comprises the following steps:
[0008] Step 1: preparing Cu-Cr-Nb alloy powder and Cu powder respectively by gas atomization powder making method;
[0009] Step 2: Mixing the Cu-Cr-Nb alloy powder prepared in step 1 and the Cu powder in a ball mill to obtain a composite powder;
[0010] Step 3: Sintering the composite powder obtained in step 2 to obtain a Cu-Cr-Nb heterostructure composite material.
[0011] The above method is characterized in that the Cu-Cr-Nb alloy powder in step 1 is composed of the following components in atomic percentage: Cr 2%~8%, Nb 1%~4%, and the remainder is Cu and unavoidable impurities, wherein the atomic ratio of Cr element to Nb element is 2:1.
[0012] The above method is characterized in that the mass of the Cu-Cr-Nb alloy powder in step 2 accounts for 50% to 95% of the total mass of the composite powder.
[0013] The above method is characterized in that the ball-to-material ratio used in the ball mill in step 2 is 3:1~10:1, the ball mill speed is 100rpm~250rpm, and the ball milling time is 3h~10h.
[0014] The invention can quickly and effectively mix two kinds of powders uniformly by controlling the ball-to-material ratio, rotation speed and time of the ball mill.
[0015] The above method is characterized in that the mixing in step 2 is carried out under vacuum or inert gas environment.
[0016] The invention is used to reduce the contact between the alloy powder and the air and prevent the alloy powder from being oxidized during the ball milling process by mixing in a vacuum or inert gas environment.
[0017] The above method is characterized in that the sintering molding in step three is vacuum packaging followed by hot pressing sintering or hot isostatic pressing sintering.
[0018] The above method is characterized in that the hot pressing sintering system is: temperature 800℃~950℃, pressure 30MPa~45MPa, and insulation time 1h~3h; the hot isostatic pressing sintering system is: temperature 700℃~850℃, pressure 100MPa~200MPa, and insulation time 1h~3h.
[0019] The present invention controls the temperature, pressure and holding time during the sintering process so that the composite powder can be formed uniformly and densely, while avoiding excessive temperature and pressure and excessive holding time to cause excessive fusion of the Cu-Cr-Nb alloy region and the Cu region inside the composite material.
[0020] The above method is characterized in that the Cu-Cr-Nb heterogeneous structure composite material in step 3 is subjected to rolling or extrusion treatment to obtain a Cu-Cr-Nb heterogeneous structure composite material plate or rod.
[0021] The above method is characterized in that the rolling temperature is 700°C~900°C, the total rolling deformation is 60%~70%; the extrusion temperature is 750°C~900°C, the extrusion speed is 220mm / min~380mm / min, and the extrusion ratio is 5:1~12:1.
[0022] The present invention controls the rolling temperature and the extrusion temperature to avoid cracking of the Cu-Cr-Nb heterostructure composite material due to too low temperature and to avoid the influence of too high temperature on the material performance of the Cu-Cr-Nb heterostructure composite material.
[0023] Compared with the prior art, the present invention has the following advantages:
[0024] 1. The present invention introduces a Cu soft area into a Cu-Cr-Nb alloy matrix, so that the prepared composite material produces heterogeneous deformation induced strengthening, which improves the yield strength and work hardening ability of the composite material while ensuring good plasticity, thereby achieving a good match between the strength and plasticity of the Cu-Cr-Nb heterostructure composite material; at the same time, the introduced micron-sized Cu grains provide a fast channel for electron transmission, so that the Cu-Cr-Nb heterostructure composite material also has excellent electrical conductivity.
[0025] 2. The Cu-Cr-Nb heterostructure composite material prepared by the present invention uses Cu to replace part of Cu-Cr-Nb, which effectively reduces the preparation cost of the Cu-Cr-Nb heterostructure composite material without affecting its strength and electrical conductivity.
[0026] 3. The present invention adopts a hot pressing sintering or hot isostatic pressing process to control the temperature, pressure and holding time during the process, so that the composite powder can be uniformly and densely formed, while ensuring that the Cu-Cr-Nb alloy region and the Cu region inside the Cu-Cr-Nb heterostructure composite material are clearly divided, effectively enhancing the back stress and normal stress, thereby improving the strength and conductivity of the Cu-Cr-Nb heterostructure composite material.
[0027] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Graph showing stress-strain test results of the Cu-Cr-Nb heterogeneous composite material plate prepared in Example 1 of the present invention and the Cu-Cr-Nb homogeneous composite material plate prepared in Comparative Example 1.
[0029] Figure 2 It is a statistical diagram of the back stress of the Cu-Cr-Nb heterogeneous structure composite material plate prepared in Example 1 of the present invention and the Cu-Cr-Nb homogeneous composite material plate prepared in Comparative Example 1.
[0030] Figure 3 The effective stress statistics diagram of the Cu-Cr-Nb heterogeneous structure composite material plate prepared in Example 1 of the present invention and the Cu-Cr-Nb homogeneous composite material plate prepared in Comparative Example 1 are shown.
[0031] Figure 4 This is a microstructure diagram of the Cu-Cr-Nb heterostructure composite material prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0032] Example 1
[0033] The Cu-Cr-Nb heterostructure composite material of this embodiment is composed of the following regions in mass percentage: 90% of the Cu-Cr-Nb alloy region and 10% of the Cu region.
[0034] The preparation method of the Cu-Cr-Nb heterostructure composite material of this embodiment comprises the following steps:
[0035] Step 1: Prepare Cu-Cr-Nb alloy powder and Cu powder respectively by gas atomization powder making method; the Cu-Cr-Nb alloy powder is composed of the following components in atomic percentage: Cr 2%, Nb 1%, and the balance is Cu and unavoidable impurities;
[0036] Step 2: Using a ball mill under vacuum environment, the Cu-Cr-Nb alloy powder prepared in step 1 and the Cu powder are mixed to obtain a composite powder; the mass of the Cu-Cr-Nb alloy powder accounts for 90% of the total mass of the composite powder, the ball-to-material ratio used in the ball mill is 5:1, the ball mill speed is 200 rpm, and the ball milling time is 6 hours;
[0037] Step 3: vacuum-packaging the composite powder obtained in step 2, and hot-pressing and sintering for 1 hour at a temperature of 800°C and a pressure of 30 MPa to obtain a Cu-Cr-Nb heterostructure composite material; rolling the Cu-Cr-Nb heterostructure composite material at 850°C for 30 minutes, with a pressing amount of 0.5 mm per pass during the hot rolling process and a total rolling deformation of 65%, to obtain a Cu-Cr-Nb heterostructure composite material sheet.
[0038] According to tests, the Cu-Cr-Nb heterogeneous structure composite material plate prepared in this embodiment has a tensile strength of 410 MPa, an elongation of 28%, and an electrical conductivity of 74% IACS.
[0039] Comparative Example 1
[0040] The difference between this comparative example and Example 1 is that the raw material of the prepared Cu-Cr-Nb homogeneous composite material plate is only the Cu-Cr-Nb alloy powder prepared by gas atomization method, and no Cu powder is added.
[0041] The stress-strain test was performed on the Cu-Cr-Nb homogeneous composite material plate prepared in Comparative Example 1 and the Cu-Cr-Nb heterogeneous composite material plate prepared in Example 1. The results are as follows: Figure 1 As shown, the stress value of the Cu-Cr-Nb homogeneous composite material plate prepared in this comparative example is lower than that of the Cu-Cr-Nb heterogeneous structure composite material plate prepared in Example 1, indicating that after the addition of Cu powder, heterogeneous deformation induced strengthening occurs inside the material, so that the Cu-Cr-Nb heterogeneous structure composite material plate has good strength-plasticity matching characteristics.
[0042] The back stress test was performed on the Cu-Cr-Nb homogeneous composite material plate prepared in Comparative Example 1 and the Cu-Cr-Nb heterogeneous composite material plate prepared in Example 1. The results are as follows: Figure 2As shown, the back stress of the Cu-Cr-Nb homogeneous composite material plate of this comparative example is much smaller than that of the Cu-Cr-Nb heterogeneous composite material plate. This is because there is a Cu region inside the Cu-Cr-Nb heterogeneous composite material plate of Example 1, and the heterogeneous microstructure will produce a large number of geometrically required dislocations (GNDs), resulting in the phenomenon of heterogeneous deformation-induced strengthening and a large amount of back stress, which can improve the strength of the plate and maintain good tensile plasticity.
[0043] The effective stress test was performed on the Cu-Cr-Nb homogeneous composite material plate prepared in Comparative Example 1 and the Cu-Cr-Nb heterogeneous composite material plate prepared in Example 1. The results are as follows: Figure 3 As shown, the effective stress of the Cu-Cr-Nb homogeneous composite material plate in this comparative example is smaller than that of the Cu-Cr-Nb heterogeneous structure composite material plate, indicating that the addition of Cu powder can effectively increase the strength of the Cu-Cr-Nb heterogeneous structure composite material plate.
[0044] Example 2
[0045] The Cu-Cr-Nb heterostructure composite material of this embodiment is composed of the following regions in terms of mass percentage: 95% of the Cu-Cr-Nb alloy region and 5% of the Cu region.
[0046] The preparation method of the Cu-Cr-Nb heterostructure composite material of this embodiment comprises the following steps:
[0047] Step 1: Prepare Cu-Cr-Nb alloy powder and Cu powder respectively by gas atomization powder making method; the Cu-Cr-Nb alloy powder is composed of the following components in atomic percentage: Cr 4%, Nb 2%, and the balance is Cu and unavoidable impurities;
[0048] Step 2: Using a ball mill under an inert gas environment, the Cu-Cr-Nb alloy powder prepared in step 1 and the Cu powder are mixed to obtain a composite powder; the mass of the Cu-Cr-Nb alloy powder accounts for 95% of the total mass of the composite powder, the ball-to-material ratio used in the ball mill is 3:1, the ball mill speed is 100 rpm, and the ball milling time is 3 hours;
[0049] Step 3: vacuum-packaging the composite powder obtained in step 2, and hot-pressing and sintering for 1 hour at a temperature of 800°C and a pressure of 30 MPa to obtain a Cu-Cr-Nb heterostructure composite material; rolling the Cu-Cr-Nb heterostructure composite material at 700°C for 30 minutes, with a pressing amount of 0.5 mm per pass during the hot rolling process and a total rolling deformation of 60%, to obtain a Cu-Cr-Nb heterostructure composite material sheet.
[0050] The Cu-Cr-Nb heterostructure composite material prepared in this example was photographed using a scanning electron microscope. Figure 4 As shown, the Cu-Cr-Nb heterostructure composite material contains Cu-Cr-Nb region with high-density precipitation phase and Cu region.
[0051] According to tests, the Cu-Cr-Nb heterogeneous structure composite material plate prepared in this embodiment has a tensile strength of 430 MPa, an elongation of 27%, and an electrical conductivity of 72% IACS.
[0052] Example 3
[0053] The Cu-Cr-Nb heterostructure composite material of this embodiment is composed of the following regions in mass percentage: the Cu-Cr-Nb alloy region is 85%, and the Cu region is 15%.
[0054] The preparation method of the Cu-Cr-Nb heterostructure composite material of this embodiment comprises the following steps:
[0055] Step 1: Prepare Cu-Cr-Nb alloy powder and Cu powder respectively by gas atomization powder making method; the Cu-Cr-Nb alloy powder is composed of the following components in atomic percentage: Cr 8%, Nb 4%, and the balance is Cu and unavoidable impurities;
[0056] Step 2: Using a ball mill under an inert gas environment, the Cu-Cr-Nb alloy powder prepared in step 1 and the Cu powder are mixed to obtain a composite powder; the mass of the Cu-Cr-Nb alloy powder accounts for 85% of the total mass of the composite powder, the ball-to-material ratio used in the ball mill is 10:1, the ball mill speed is 250 rpm, and the ball milling time is 10 h;
[0057] Step 3: vacuum-packaging the composite powder obtained in step 2, and hot-pressing and sintering for 3 hours at a temperature of 950°C and a pressure of 45 MPa to obtain a Cu-Cr-Nb heterostructure composite material; rolling the Cu-Cr-Nb heterostructure composite material at 900°C for 30 minutes, with a pressing amount of 0.5 mm per pass during the hot rolling process and a total rolling deformation of 70%, to obtain a Cu-Cr-Nb heterostructure composite material sheet.
[0058] According to tests, the Cu-Cr-Nb heterostructure composite material plate prepared in this embodiment has a tensile strength of 450 MPa, an elongation of 25%, and an electrical conductivity of 75% IACS.
[0059] Example 4
[0060] The Cu-Cr-Nb heterostructure composite material of this embodiment is composed of regions with the following mass percentages: 50% Cu-Cr-Nb alloy region and 50% Cu region.
[0061] The preparation method of the Cu-Cr-Nb heterostructure composite material of this embodiment comprises the following steps:
[0062] Step 1: Prepare Cu-Cr-Nb alloy powder and Cu powder respectively by gas atomization powder making method; the Cu-Cr-Nb alloy powder is composed of the following components in atomic percentage: Cr 8%, Nb 4%, and the balance is Cu and unavoidable impurities;
[0063] Step 2: Using a ball mill under an inert gas environment, the Cu-Cr-Nb alloy powder prepared in step 1 and the Cu powder are mixed to obtain a composite powder; the mass of the Cu-Cr-Nb alloy powder accounts for 50% of the total mass of the composite powder, the ball-to-material ratio used in the ball mill is 8:1, the ball mill speed is 210 rpm, and the ball milling time is 4 hours;
[0064] Step 3: vacuum-pack the composite powder obtained in step 2, and perform hot pressing and sintering for 2 hours at a temperature of 900°C and a pressure of 40 MPa to obtain a Cu-Cr-Nb heterogeneous structure composite material; the Cu-Cr-Nb heterogeneous structure composite material is rolled at 900°C for 30 minutes, with a pressing amount of 0.5 mm per pass during the hot rolling process and a total rolling deformation of 70%, to obtain a Cu-Cr-Nb heterogeneous structure composite material sheet.
[0065] According to tests, the Cu-Cr-Nb heterostructure composite material plate prepared in this embodiment has a tensile strength of 400 MPa, an elongation of 30%, and an electrical conductivity of 82% IACS.
[0066] Example 5
[0067] The Cu-Cr-Nb heterostructure composite material of this embodiment is composed of the following regions in mass percentage: 80% of the Cu-Cr-Nb alloy region and 20% of the Cu region.
[0068] The preparation method of the Cu-Cr-Nb heterostructure composite material of this embodiment comprises the following steps:
[0069] Step 1: Prepare Cu-Cr-Nb alloy powder and Cu powder respectively by gas atomization powder making method; the Cu-Cr-Nb alloy powder is composed of the following components in atomic percentage: Cr 2%, Nb 1%, and the balance is Cu and unavoidable impurities;
[0070] Step 2: Using a ball mill under an inert gas environment, the Cu-Cr-Nb alloy powder prepared in step 1 and the Cu powder are mixed to obtain a composite powder; the mass of the Cu-Cr-Nb alloy powder accounts for 80% of the total mass of the composite powder, the ball-to-material ratio used in the ball mill is 7:1, the ball mill speed is 250 rpm, and the ball milling time is 10 h;
[0071] Step 3: vacuum-packaging the composite powder obtained in step 2, and hot isostatic pressing sintering for 1 h at a temperature of 700°C and a pressure of 100 MPa to obtain a Cu-Cr-Nb heterogeneous structure composite material; extruding the Cu-Cr-Nb heterogeneous structure composite material at 750°C, with an extrusion speed of 220 mm / min and an extrusion ratio of 5:1 to obtain a Cu-Cr-Nb heterogeneous structure composite material rod.
[0072] According to tests, the tensile strength of the Cu-Cr-Nb heterostructure composite material rod prepared in this embodiment is 410 MPa, the elongation is 32%, and the electrical conductivity is 78% IACS.
[0073] Example 6
[0074] The Cu-Cr-Nb heterostructure composite material of this embodiment is composed of the following regions in mass percentage: 90% of the Cu-Cr-Nb alloy region and 10% of the Cu region.
[0075] The preparation method of the Cu-Cr-Nb heterostructure composite material of this embodiment comprises the following steps:
[0076] Step 1: Prepare Cu-Cr-Nb alloy powder and Cu powder respectively by gas atomization powder making method; the Cu-Cr-Nb alloy powder is composed of the following components in atomic percentage: Cr 6%, Nb 3%, and the balance is Cu and unavoidable impurities;
[0077] Step 2: Using a ball mill under an inert gas environment, the Cu-Cr-Nb alloy powder prepared in step 1 and the Cu powder are mixed to obtain a composite powder; the mass of the Cu-Cr-Nb alloy powder accounts for 90% of the total mass of the composite powder, the ball-to-material ratio used in the ball mill is 6:1, the ball mill speed is 250 rpm, and the ball milling time is 10 h;
[0078] Step 3: vacuum-packaging the composite powder obtained in step 2, and hot isostatic pressing sintering for 2 hours at a temperature of 800°C and a pressure of 150 MPa to obtain a Cu-Cr-Nb heterogeneous structure composite material; extruding the Cu-Cr-Nb heterogeneous structure composite material at 800°C, with an extrusion speed of 300 mm / min and an extrusion ratio of 10:1 to obtain a Cu-Cr-Nb heterogeneous structure composite material rod.
[0079] According to tests, the tensile strength of the Cu-Cr-Nb heterostructure composite material rod prepared in this embodiment is 447 MPa, the elongation is 29%, and the electrical conductivity is 74% IACS.
[0080] Example 7
[0081] The Cu-Cr-Nb heterostructure composite material of this embodiment is composed of the following regions in mass percentage: the Cu-Cr-Nb alloy region is 70%, and the Cu region is 30%.
[0082] The preparation method of the Cu-Cr-Nb heterostructure composite material of this embodiment comprises the following steps:
[0083] Step 1: Prepare Cu-Cr-Nb alloy powder and Cu powder respectively by gas atomization powder making method; the Cu-Cr-Nb alloy powder is composed of the following components in atomic percentage: Cr 4%, Nb 2%, and the balance is Cu and unavoidable impurities;
[0084] Step 2: Using a ball mill under vacuum environment, the Cu-Cr-Nb alloy powder prepared in step 1 and the Cu powder are mixed to obtain a composite powder; the mass of the Cu-Cr-Nb alloy powder accounts for 70% of the total mass of the composite powder, the ball-to-material ratio used in the ball mill is 8:1, the ball mill speed is 200 rpm, and the ball milling time is 8 hours;
[0085] Step 3: vacuum-packaging the composite powder obtained in step 2, and hot isostatic pressing sintering for 3 hours at a temperature of 850°C and a pressure of 200 MPa to obtain a Cu-Cr-Nb heterogeneous structure composite material; extruding the Cu-Cr-Nb heterogeneous structure composite material at 900°C, with an extrusion speed of 380 mm / min and an extrusion ratio of 12:1 to obtain a Cu-Cr-Nb heterogeneous structure composite material rod.
[0086] According to tests, the tensile strength of the Cu-Cr-Nb heterostructure composite material rod prepared in this embodiment is 436 MPa, the elongation is 31%, and the electrical conductivity is 83% IACS.
[0087] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent structural transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A deformation induced strengthened Cu-Cr-Nb heterostructure composite material, characterized in that: The area consisting of the following mass percentages Composition: Cu-Cr-Nb alloy region is 50%~95%, Cu region is 5%~50%; the composite material is prepared by the following method: Step 1: preparing Cu-Cr-Nb alloy powder and Cu powder respectively by gas atomization powder making method; Step 2: Using a ball mill to mix the Cu-Cr-Nb alloy powder prepared in step 1 with Cu powder to obtain a composite powder; Step three, sintering the composite powder obtained in step two to obtain a Cu-Cr-Nb heterostructure composite material; the sintering molding is hot pressing sintering or hot isostatic pressing sintering after vacuum packaging, and the hot pressing sintering system is: temperature 800°C~950°C, pressure 30MPa~45MPa, and insulation time 1h~3h; the hot isostatic pressing sintering system is: temperature 700°C~850°C, pressure 100MPa~200MPa, and insulation time 1h~3h.
2. The material according to claim 1, characterized in that The Cu-Cr-Nb alloy powder in step 1 is composed of the following atomic percentages: Composition: Cr 2%~8%, Nb 1%~4%, the balance is Cu and unavoidable impurities, among which the atomic ratio of Cr to Nb is 2:
1.
3. The material according to claim 1, characterized in that The mass of the Cu-Cr-Nb alloy powder in step 2 accounts for 50% to 95% of the total mass of the composite powder.
4. The material according to claim 1, characterized in that The ball-to-material ratio used in the ball mill in step 2 is 3:1-10:1, the ball mill speed is 100 rpm-250 rpm, and the ball milling time is 3 h-10 h.
5. The material according to claim 1, characterized in that The mixing in step 2 is performed under vacuum or inert gas environment.
6. The material according to claim 1, characterized in that The Cu-Cr-Nb heterogeneous structure composite material in step 3 is rolled or extruded to obtain a Cu-Cr-Nb heterogeneous structure composite material plate or rod.
7. The material according to claim 6, characterized in that The rolling temperature is 700° C. to 900° C., and the total rolling deformation is 60% to 70%; the extrusion temperature is 750° C. to 900° C., the extrusion speed is 220 mm / min to 380 mm / min, and the extrusion ratio is 5:1 to 12:1.
Citation Information
Patent Citations
Copper-based self-lubricating composite material and preparation method thereof
CN114000007A
Element alloying preparation method of metal matrix composite material with three-peak grain structure
CN114318039A